Динамика напряжённо-деформированного состояния элементов цепного привода в металлическом и полимерном исполнении - Пилипенко, О. И.; Полуян, А. В. (НТУ "ХПИ", 2015)
Показан новый подход к расчёту динамики напряжённо-деформированного состояния элементов цепных передач, учитывающий реальные динамические процессы, неизбежно сопровождающие работу цепных приводов. Рассмотрено изменение: динамических нагрузок, действующих в двухмассовых цепных контурах, необходимой мощности цепных приводов, а также распределения напряжений, результирующих перемещений, коэффициента запаса прочности пластин звеньев металлического приводного роликового цепного контура и упругого монолитного звена полимерной цепи.

A new approach to the calculation of the dynamics of the stress-strained state of chain transmissions are shown, which takes into account the real dynamic processes occurring during operation of chain drives. Maximum stress of a monolithic elastic polymeric link is less than the internal metal plate of the chain link. In the event of the maximum (peak) stress occurs and the corresponding maximum (peak) resulting elastic movement in the nodes of elements of the chain inve of the minimum safety factor of the material investigated elements of the chain. In addition, the obtained average value of the minimum safety factor plates metal chain corresponds to the traditional high value for such chains, and for the polymer chain, this value is placed within the machine-building norms. The existence of emerging vibration loads that multiple act on the sprockets and chain contour during operation of transmission. They are concentrated in the areas of microshock interaction roller chain with sprockets and, as a result of such influence, there are large localized stresses and elastic displacements in the material, which in most cases is the reason for breaking the plates of the chain links.
Dynamics of the stress-strained state the elements of a chain drive in in metal and polymeric implementation
Keywords: цепные передачи; совокупность напряжений; приводные роликовые цепи; вибрационные нагрузки; пластины звеньев цепи; plates of the chain links; elastic polymer; monolithic link